2017
DOI: 10.1371/journal.pone.0177750
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and apoptotic remodeling in autonomic nervous system following myocardial infarction

Abstract: BackgroundChronic myocardial infarction (MI) triggers pathological remodeling in the heart and cardiac nervous system. Abnormal function of the autonomic nervous system (ANS), including stellate ganglia (SG) and dorsal root ganglia (DRG) contribute to increased sympathoexcitation, cardiac dysfunction and arrythmogenesis. ANS modulation is a therapeutic target for arrhythmia associated with cardiac injury. However, the molecular mechanism involved in the pathological remodeling in ANS following cardiac injury r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
0
34
0
1
Order By: Relevance
“…Quantification of cardiomyocyte apoptosis by colocalization of tropomyosin and DNA fragmentation. Formalin-fixed and paraffinembedded transverse ventricular heart sections from each mouse were used to colocalize expression of tropomyosin, a myocardium marker, and TUNEL for the detection of apoptosis (13,31). Briefly, after deparaffinization and rehydration, heart sections received antigen retrieval in citrate buffer (pH 6.0) with boiling for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of cardiomyocyte apoptosis by colocalization of tropomyosin and DNA fragmentation. Formalin-fixed and paraffinembedded transverse ventricular heart sections from each mouse were used to colocalize expression of tropomyosin, a myocardium marker, and TUNEL for the detection of apoptosis (13,31). Briefly, after deparaffinization and rehydration, heart sections received antigen retrieval in citrate buffer (pH 6.0) with boiling for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…According to Wang et al (2010) [ 179 ], cardiac remodeling which is an adaptive process often leads to electrical instability, ventricular arrhythmia, cardiac dysfunction, and the death of cardiomyocytes. The incidence of cardiac dysfunction, arrhythmogenesis, and myocardial infarction has been linked to an increase of sympathetic excitation during the remodeling of ANS function as seen in the starred ganglia and dorsal root ganglia [ 180 ]. The ganglionic compromise of the autonomic plexuses during adolescence increases susceptibility to atrial fibrillation, micro- and macrostructural changes in the atrial myocardium, intracellular damage (myocyte degeneration, apoptosis), and extracellular fibrotic proliferation [ 181 ].…”
Section: General Discussion and Perspectivementioning
confidence: 99%
“…Using horseradish peroxidase (HRP), our previous works tested by retrograde tracing showed that the cervical and upper thoracic dorsal root ganglia were related to the signaling transmission induced by MI ( Liu et al, 2013 ; Tu et al, 2013 ). It was reported that changes in gene expression localized to thoracic spinal cord only, with no change in gene expression in lumber DRG after MI or infarction and the expression of immune modulators and apootic genes were observed in the thoracic DRG but not in the lumbar DRG following MI ( Gao et al, 2017 ). Our results showed that the expression changes of P2Y 12 mRNA and protein localized to cervical and upper thoracic spinal cord DRGs only and no changes were observed for the expression of P2Y 12 mRNA and protein in lumbar DRGs from the same post-MI animals.…”
Section: Discussionmentioning
confidence: 99%